2007
DOI: 10.1021/bi7000664
|View full text |Cite
|
Sign up to set email alerts
|

Bioflavonoids as Poisons of Human Topoisomerase IIα and IIβ

Abstract: Bioflavonoids are human dietary components that have been linked to the prevention of cancer in adults and the generation of specific types of leukemia in infants. While these compounds have a broad range of cellular activities, many of their genotoxic effects have been attributed to their actions as topoisomerase II poisons. However, the activities of bioflavonoids against the individual isoforms of human topoisomerase II have not been analyzed. Therefore, we characterized the activity and mechanism of action… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
179
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 157 publications
(194 citation statements)
references
References 106 publications
9
179
0
Order By: Relevance
“…30 In this context, the genotoxic activity of some human dietary components such as bioflavonoid has been attributed to their action as topoisomerase poisons. 5 In this study, we demonstrate through docking simulations that RSV polar groups allow this molecule to establish non-covalent cross-linking interactions with both TOPOII and DNA at the binding interface between these two macromolecules. This result is particularly interesting in that it is suggestive of a stabilizing effect of RSV on the TOPOII/DNA complex which, in turn, could cause a delay in DNA religation.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…30 In this context, the genotoxic activity of some human dietary components such as bioflavonoid has been attributed to their action as topoisomerase poisons. 5 In this study, we demonstrate through docking simulations that RSV polar groups allow this molecule to establish non-covalent cross-linking interactions with both TOPOII and DNA at the binding interface between these two macromolecules. This result is particularly interesting in that it is suggestive of a stabilizing effect of RSV on the TOPOII/DNA complex which, in turn, could cause a delay in DNA religation.…”
Section: Discussionmentioning
confidence: 83%
“…3 It has been suggested that some of the cellular effects of polyphenols, such as anti-proliferative and proapoptotic actions, could be correlated with their ability to act on topoisomerases. 4,5 These are ubiquitous nuclear enzymes that modulate the topological state of DNA by breaking and resealing one or both strands of a DNA duplex. In eukaryotic cells, type II topoisomerases, isoforms a and b, function during major cellular processes involving DNA (recombination, replication, proper chromosome structure and segregation) generating intermediate cleavable or covalent complexes with a short half-life.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…They represent the most abundant natural source of antioxidants, potently inhibit tyrosine kinases, and exhibit anti-proliferative and pro-apoptotic affects leaves [105][106][107][108][109][112][113][114][115][116]. However, they also display cytotoxic and genotoxic properties and many are potent topoisomerase II poisons [117][118][119][120]. Although the physiological actions of bioflavonoids are complex, the sensitivity of cells to genistein-induced toxicity has been correlated to the activity of the type II enzyme [119,121].…”
Section: Non-covalent Topoisomerase II Poisonsmentioning
confidence: 99%
“…Soy is a very important constituent in Asian and vegetarian nutrition [2], and represents a huge economic impact on society. Additionally, epidemiological studies suggest that GEN helps to protect against cancer [3][4][5][6][7], cardiovascular diseases [8], osteoporosis [9], age-related diseases [10] and inflammation processes [11]. Probably the most attractive activity of this bioflavonoid is its promising chemopreventive activity, which works by inducing either G 2 /M or G 0 /G 1 cell cycle arrest depending on the cell line [12][13][14].…”
Section: Introductionmentioning
confidence: 99%